The relationship between SCI editorial board representation and university research output in the field of computer science: A quantile regression approach - Wang, Xing (Malaysian Journal of Library and Information Science, 2018)
This study uses the quantile regression models to explore the relationship between SCI (Science Citation Index) editorial board representation and research output of universities in the field of computer science. Quantile regression allows the investigation of the variation of the relationship between editorial board representation and research output. A total of 447 journals and 14,442 editorial board members were analysed. The results suggest that the number of editorial board members is positively and significantly related to the quantity (number of articles) and impact (total number of citations and citations per paper) of the research output from their respective universities. A deeper analysis using quantile regression, indicates that the relationship between the number of editorial board members and the research output is stronger when the university is at the higher quartile of the conditional research output distribution. In addition, to speculate on possible mechanisms behind the relationship between editorial board representation and research output, two exploratory studies based on two small samples were conducted at the individual and journal level, respectively.